Effects of Mergers and Acquisitions on Shareholder Wealth: Event Study for Latin American Airlines (2015)
This study analyzes the effectof changes in corporate controlon the way shareholdersbenefit from the announcements of selling and buying airlines, thus contributing to the literature on mergers and acquisitions (M&As) in emerging markets. Using a methodologyof event study, including GARCH and OLS models, we find evidence that some selling companies obtain abnormal returns that are statisticallysignificant after the announcement of the M&A. However, when the merger is not strategic, the companies present statisticallysignificant negative abnormal returns. The resultsare not conclusive when analyzing the effecton the valueof the buying companies.